Road Transportation Management Potentiality Enhancement for Linking Special Economic Zones and Border Trade Activities in Mukdahan Province, Thailand - Setthachotsombut, Natpatsaya (ExcelingTech, 2020)
Abstract— The purpose of this article is to study the knowledge, to create a model for improving the Road Transportation Management Potentiality for linking the special economic zone and border trade in Mukdahan province, Thailand, and to study the effect of increasing the potential of road transport management on business performance. Mixed research method was used. The sample was 316 road freight entrepreneurs in the border economic and trade areas in Mukdahan province, from a population of 1,500 people, including 12 interviewees. Data were collected by using questionnaires and interview forms. The data gathered was tested by using various statistical techniques to ensure that the information is reliable and accurate in Structural Equation Modeling (SEM). The results found that increasing the potential of road transport management for linking special economic zones and border trade in Mukdahan province with Inbound-Outbound Transportation (IOT) had a direct positive impact on Performance of Firm Management (PFM), with the three most important capabilities: security, documentation procedures, and vehicle management, whereas the three most outstanding results are cheaper, faster, and better. To implement this model, entrepreneurs, therefore, need to give first priority in developing operational manuals such as safety standard transportation manual, customs clearance from Mukdahan province to Laos PDR manual, and vehicle management manual.